Changes of protein content and its fractions in bovine milk from different breeds subject to somatic cell count - Litwińczuk, Z.; Król, J.; Brodziak, A.; Barłowska, J. (Journal of dairy science, 2011)
Global milk production is undeniably dominated by 2 dairy breeds recognized worldwide: Holstein-Friesian and Jersey. A third breed, Simmental, serves as a dual-purpose breed. The objective of the present research was to establish potential changes in the fractional components of bovine milk protein (mainly whey) in relation to the health status of a dairy cow's mammary glands, which is closely determined by somatic cell count (SCC). The milk of 3 breeds was studied: Polish Holstein-Friesian (Black and Red-White varieties), Simmental, and Jersey. The cows were housed in freestall barns and fed according to the total mixed ration feeding system for both winter and summer periods. Milk samples were collected individually from each cow twice a year, in the winter and summer seasons. A total of 1,822 milk samples were evaluated (946 in winter and 876 in summer). The milk was examined for SCC, crude protein, casein, and whey fraction proteins (α-lactalbumin, β-lactoglobulin, lactoferrin, BSA, and lysozyme). The research material for each breed was split into 4 groups based on SCC (group I: ≤100,000 cells/mL; group II: 101,000 to 400,000 cells/mL; group III: 401,000 to 500,000 cells/mL; and group IV: 501,000 to 1,000,000 cells/mL). It was found that an increase of SCC promulgated a progressive decline in the daily yield of milk, which was significantly true for the Polish Holstein-Friesian. The level of crude protein decreased slightly as SCC increased, and casein concentration (r=−0.591) also followed this trend of decline. Elevation of SCC produced a decrease of major albumins (i.e., α-lactalbumin and β-lactoglobulin). However, SCC increase induced an increase in the immunoactive proteins (lactoferrin and lysozyme) as well as BSA. The interactions of a breed with increased SCC, which can be measured based on the BSA content of the milk, has indicated various levels of susceptibility to the increase in different breeds. This is confirmed by different values of correlation coefficients for these relationships: 0.71 in the Holstein-Friesian, 0.58 in Simmental, and 0.47 in the Jersey cows. Holstein-Friesian cows are more sensitive to mammary gland infections causing a greater decline of their daily milk yields, which, in turn, is reflected in an increase of the negative value of the correlation coefficients between SCC and milk efficiency (−0.24). In the other 2 breeds, the correlations were also negative, but substantially lower (−0.12 and −0.15).